Young and technology, communicative interation y generational transformation - Lopez Camacho, Adriana; Duarte Valencia, Felipe Alberto (Visión electrónica, 2014)
The current article contains a historical path about corporal transformation and technological affectations in youthful bodies in generational way from a documentary analysis of youthful bodies and their features of each era. Therefore three set dates will be analyzed by Margaret Mead in her book culture and compromise a study about generational rapture that will help us find on the cultural raptures in tree different times 1929 figurative post culture, 1973 configurative culture and culture revolution and 2001 prefigurative culture and the entrance to the social otherness. in this order of ideas I would say three youthful transformations in each era have different features of the reality and the world that surrounds it.